2017
DOI: 10.1145/3155055.3155065
|View full text |Cite
|
Sign up to set email alerts
|

How to Measure the Killer Microsecond

Abstract: Datacenter-networking research requires tools to both generate traffic and accurately measure latency and throughput. While hardwarebased tools have long existed commercially, they are primarily used to validate ASICs and lack flexibility, e.g., to study new protocols. They are also too expensive for academics. The recent development of kernel-bypass networking and advanced NIC features such as hardware timestamping have created new opportunities for accurate latency measurements. This paper compares these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The Middlebox machine runs one of the four NFs mentioned above (we use one core). The Tester machine runs MoonGen [22] to generate traffic and measure packet loss, throughput, and latency; for the latency measurements, we rely on hardware timestamps for better accuracy [49]. We use DPDK v. 16.07 on Ubuntu Linux with kernel 3.13.0-119-generic.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…The Middlebox machine runs one of the four NFs mentioned above (we use one core). The Tester machine runs MoonGen [22] to generate traffic and measure packet loss, throughput, and latency; for the latency measurements, we rely on hardware timestamps for better accuracy [49]. We use DPDK v. 16.07 on Ubuntu Linux with kernel 3.13.0-119-generic.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Dedicated timestamping hardware [35,36] offers line-rate high-precision and high-accuracy timestamping on multiple 10G Ethernet ports but requires additional hardware, increasing the costs of the measurement setup. A study by Primorac et al [37] compared MoonGen's timestamping to various software and hardware timestamping solutions. They concluded that MoonGen's hardware timestamping method offers a similar accuracy and precision compared to a professional timestamping hardware solution.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Switching off energysaving mechanisms can improve latency beyond the 99.99th percentile by approx. 10 s according to Primorac et al [37].…”
Section: Os-specific Techniquesmentioning
confidence: 99%